Dietary inflammatory potential and the incidence of depression and anxiety: a meta-analysis - Xiaoling Li; Meicui Chen; Zhicui Yao; Tianfeng Zhang; Zengning Li (BMC, 2022)
Abstract The potential modifiable role of diet in common psychological disorders, including depression and anxiety, has attracted growing interest. Diet may influence the occurrence of mental disorders through its inflammatory characteristics. The purpose of this meta-analysis was to explore whether dietary inflammatory potential is associated with the risk of depression and anxiety. A systematic literature search was conducted in PubMed, Web of Science, and Embase databases up to February 2021. Articles related to dietary inflammatory potential and risk of depression or anxiety were included. After the elimination of repetitive and irrelevant literature, we conducted quality assessment, publication bias, and sensitivity analysis. In total, 17 studies with a total of 157,409 participants were included in the final analysis. Compared with the lowest inflammatory diet group, the highest group was significantly associated with the incidence of depression and anxiety, with the following pooled odds ratios (ORs) and 95% confidence intervals (95% CIs): 1.45 (1.30 ~ 1.62) for depression and 1.66 (1.41 ~ 1.96) for anxiety. A subgroup analysis by gender showed that this association was more prominent in women. For depression, the increased risk was 49% in women (OR 1.49, 95% CI 1.28 ~ 1.74) and 27% in men (OR 1.27, 95% CI 1.06 ~ 1.52). As for anxiety, the increased risk was 80% in women (OR 1.80, 95% CI 1.30 ~ 2.49) and 47% in men (OR 1.53, 95% CI 0.81 ~ 2.89). As a result, long-term anti-inflammatory eating patterns may prevent depression and anxiety, whereas pro-inflammatory eating patterns may promote these conditions. People should add more fish, fish oil, fresh fruit, walnuts, and brown rice to their diet.